Improving Children's Cognitive, Affective, and Psychomotor Intelligence Through Learning Curriculum in Sunday Schools: Peningkatan Kecerdasan Kognitif, Afektif, dan Psikomotorik Anak Melalui Kurikulum Pembelajaran di Sekolah Minggu - Daniel Supriyadi (Sekolah Tinggi Teologi Baptis Indonesia, 2022)
Organizing a good education for the future of the church is important, one of which is Sunday school education. Many churches are not serious in providing education for Sunday schools. Where Sunday school only runs perfunctory, does not have a clear purpose, and is carried out by teachers who are less competent and do not use learning references. For this reason, the author wants to describe the competencies that Sunday school teachers must have in order to carry out education properly. So, through the qualitative descriptive analysis method, it can be concluded that the Sunday School Teacher Competence in Improving Children's Cognitive, Affective, and Psychomotor Intelligence Through the Learning Curriculum. The education held must be carried out by a teacher who has competence in teaching, in addition to instilling the values of Christ in carrying out learning in Sunday schools, the education carried out for Sunday schools is also important to pay attention to whether the learning carried out covers the cognitive, affective, and psychomotor. So that in addition to children understanding God's word, children can also be doers of the word. Apply God's word in their lives.